Sistem Pemantau Pencemaran Air Sungai Berbasis IoT dan Komunikasi Lora - Rasyid Achmad Fauzi; Kurniawan Irianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
River water quality degradation is a significant environmental issue that endangers aquatic ecosystems and public health. Monitoring systems face limitations related to data acquisition latency and operational range, particularly in remote locations. This study presents the design and implementation of an Internet of Things (IoT)-based river water quality monitoring system for real-time pH and Total Dissolved Solids (TDS) measurement. The system architecture consists of an Arduino Uno-based sensor node that acquires data and transmits it via a Long Range Communication (LoRa) module to an ESP32-based gateway. The gateway then stores the data on a Firebase cloud server for visualization on a custom web interface. Test results show a 100% success rate of LoRa data transmission over a distance of 20 meters with an average end-to-end system latency of 3.08 seconds. These findings demonstrate that the developed system can be a highly responsive solution for early detection of contamination, thus supporting faster intervention efforts for aquatic ecosystem protection and public health.